2019
DOI: 10.1074/jbc.ac119.008881
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Tyr-950 in the proteasome scaffolding protein RPN2 modulates its interaction with the ubiquitin receptor RPN13

Abstract: Protein substrates are targeted to the 26S proteasome through several ubiquitin receptors. One of these receptors, RPN13, is recruited to the proteasome by binding of its N-terminal pleckstrin-like receptor of ubiquitin (PRU) domain to C-terminal residues of the scaffolding protein RPN2. The RPN13 PRU domain is followed by a flexible linker and a C-terminal deubiquitylase adaptor (DEUBAD) domain, which recruits and activates the deubiquitylase UCH37. Both RPN13 and UCH37 have been implicated in human cancers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 55 publications
(58 reference statements)
0
9
0
Order By: Relevance
“…We previously speculated that the difference in sensitivity between CML and normal progenitors to knockdown of PSMD1 or PSMD3 may be due to differences in post-translational modifications, which could alter peptide targets in malignant versus normal tissues [ 31 ]. Indeed, Hemmis et al recently reported that PSMD1 can be phosphorylated at tyrosine 950, and that this modulates interactions between ubiquitin receptors [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…We previously speculated that the difference in sensitivity between CML and normal progenitors to knockdown of PSMD1 or PSMD3 may be due to differences in post-translational modifications, which could alter peptide targets in malignant versus normal tissues [ 31 ]. Indeed, Hemmis et al recently reported that PSMD1 can be phosphorylated at tyrosine 950, and that this modulates interactions between ubiquitin receptors [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…RA413S and RA414 also both show stronger binding to their 42kDa protein target, previously identified as RPN13, in ovarian cancer cell lysates than RA183. Although these reactive compounds have potential for off-target effects [50], RA190 and related inhibitors bind to cysteine 88 within a groove of RPN13 that mediates binding to the proteasome via RPN2 [16,17]. This suggests that drug blockade of RPN13 association to the 19S RP inhibits both proteasomal degradation and deubiquitinase activity of its binding partner UCH37.…”
Section: Discussionmentioning
confidence: 99%
“…The small molecule RA190 [11][12][13] was identified as the prototypic inhibitor of RPN13, and more potent analogs RA183 [14] and RA375 [15] were generated. Each of these molecules is a Michael acceptor that adducts RPN13 Cysteine 88 that resides within a groove required for binding of RPN13 to the proteasome via RPN2 [16,17], as well as other cellular proteins at higher concentrations [18,19]. However, in cytotoxicity assays, these RPN13 inhibitors (iRPN13) are not as potent as bortezomib based upon their IC50 against cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Since RPN13 is over expressed in cancer [17], Kisselev has hypothesized that the covalent RA inhibitors block both ends of the proteasome, whereas in normal cells only one end is block and the other can utilize alternative ubiquitin receptors to maintain some proteasome function [14]. However, recent structural data suggest that these RA inhibitors act to prevent RPN2 binding and thus association with the 19S RP [4,59].…”
Section: Discussionmentioning
confidence: 99%